Differential impact of stress on hypothalamic-pituitary-adrenal axis: gene expression changes in Lewis and Fisher rats - Ergang, Peter; Vodička, Martin; Soták, Matúš; Klusoňová, Petra; Behuliak, Michal; Řeháková, Lenka; Zach, Petr; Pácha, Jiří (Psychoneuroendocrinology, 2015)
The aim of the present work was to study the influence of variable stress on the expression of 11β-hydroxysteroid dehydrogenase type 1 (11HSD1) and the neuropeptides corticotropin-releasing hormone (CRH), urocortins 2 and 3(UCN2, UCN3), arginine vasopressin (AVP), oxytocin (OXT) and adenylate cyclase-activating polypeptide (PACAP) in two inbred rat strains: stress hypo-responsive Lewis (LEW) and hyper-responsive Fisher 344 (F344) rats. We found site-specific and strain-dependent differences in the basal and stress-stimulated expression of 11HSD1, CRH, UCN2, UCN3 and PACAP. In LEW rats, stress upregulated 11HSD1 in the prefrontal cortex and lateral amygdala, whereas in F344 rats 11HSD1 was upregulated in the central amygdala and hippocampal CA2 and ventral but not dorsal CA1 region; no effect was observed in the paraventricular nucleus, pituitary gland and adrenal cortex of both strains. The expression of glucocorticoid receptors did not parallel the upregulation of 11HSD1. Stress also stimulated the expression of paraventricular OXT, CRH, UCN3 and PACAP in both strains but amygdalar CRH only in LEW and UCN2/UCN3 in F344 rats, respectively. The upregulation of PACAP and CRH was paralleled only by increased expression of PACAP receptor PAC1 but not CRH receptor type 1. These observations provide evidence that inbred F344 and LEW rats exhibit not only the well-known phenotypic differences in the activity of the HPA axis but also strain- and stress-dependent differences in the expression of genes encoding 11HSD1 and neuropeptides associated with the HPA axis activity. Moreover, the differences in 11HSD1 expression suggest different local concentration of corticosterone and access to GR in canonical and noncanonical structures of the HPA axis.
Keywords: hypofyzární adenylátcyklázu aktivující peptid; Amygdala; Pituitary Gland; Gene Expression Profiling; prefrontální mozková kůra; kůra nadledvin; messenger RNA; potkani inbrední LEW; Prefrontal Cortex; Pituitary-Adrenal System; zvířata; amygdala; Corticotropin-Releasing Hormone; Hippocampus; Rats, Inbred Lew; Animals; Adrenal Cortex; Hypothalamo-Hypophyseal System; Pituitary Adenylate Cyclase-Activating Polypeptide; systém hypofýza - nadledviny; Stress, Psychological; 11-beta-hydroxysteroiddehydrogenasa typ 1; Oxytocin; arginin vasopresin; urokortiny; hormon uvolňující kortikotropin; potkani inbrední F344; RNA, Messenger; nucleus paraventricularis hypothalami; Receptors, Glucocorticoid; Rats, Inbred F344; Rats; oxytocin; Paraventricular Hypothalamic Nucleus; 11-beta-Hydroxysteroid Dehydrogenase Type 1; hipokampus; Brain; Arginine Vasopressin; psychický stres; krysa rodu Rattus; hypofýza; systém hypotalamus-hypofýza; receptory glukokortikoidů; stanovení celkové genové exprese; Urocortins; mozek